Antinociceptive activity investigation of the methanolic crude extract of Costus speciosus in Mice - Azam, Shofiul; Ansari, Prawej; Jalil, Shahnaz; Ibrahim, Abdunasir Hussain; Sultana, Nasrin; Hossain, Mohammad Mosharraf; Naveed, Jaysee Muhammad; Hossain, Mohammed Forhad (Progress in Nutrition, 2016)
Goal: This study was designed to investigate the anti-inflammatory and analgesic activity of one of common Bangladeshi medicinal plant, Costus speciosus. Methods & materials: We have included the phytochemical investigation before proceeding to our major objective. The seeds of Costus speciosus (MECS) were extracted using methanol. MECS have been used in in vitro and in vivo investigation for possible analgesic and anti-inflammatory effect. In this pre-designed study Formalin-induced writhing test and Tail immersion test was included. Results: The methanol extract of C. speciosus (at 500 mg/kg) showed significant (P